The relationship between an employee’s anxiety and depression symptoms, job satisfaction, and turnover intention in tipped vs. non-tipped employees - Fink, Anthony Jerome (Kansas State University, 2023)
The stress levels experienced by Americans is steadily increasing in response to the pandemic and has continued too today. Subsequently, the number of individuals experiencing anxiety rose to 19.1% of the population, while 6.7% experienced depression. The impact these two disorders have on individuals is great and results in missed days of work, and in some cases leads to job turnover if the employee perceives the workplace to be the cause of their mental health issues. Further, eight million American restaurant employees’ lives changed in 2020 as a result of the Covid-19 pandemic, which has only exacerbated the mental health issues of those working on the front lines of restaurants from coast to coast. The purpose of this study was to understand the impact anxiety and depression have on restaurant industry employees. Specifically, this research sought to explore if employee mental health was related to an employee’s job satisfaction and turnover intention. To accurately measure these aspects, a 45-item survey consisting of the Patient Health Questionnaire Anxiety and Depression Scale, the Minnesota Satisfaction Questionnaire short form, three questions related to turnover intention, and seven demographic questions were utilized. Means and standard deviations were computed to accurately compare each section of the survey. Then, t-tests were conducted on the differing severity levels of anxiety and depression. After conducting t-tests, the severity groupings were grouped into primary compensation type to allow for more t-tests to be run to understand the relationship between compensation and a restaurant employee’s mental health. Results noted that those who experience anxiety and depression symptoms at an increased severity level were deemed to experience higher levels of job satisfaction than their less afflicted counterparts, which is in direct contradiction to the literature available presently. Comparatively, those experiencing higher severity levels of anxiety and depression symptoms experienced higher levels of turnover intention. To further these findings, the need to determine if personal or work-related anxiety and depression drove turnover intention is great. While compensation was found to have no impact on the manifestation of either anxiety or depression symptoms, it remains a topic for further research as politics in America continue to vie for a minimum wage increase. Future research would benefit from an increase in specificity of the main symptoms of anxiety and depression being experienced by restaurant employees, and thus, to understand further the changes restauranteurs could make to benefit their businesses.
Keywords: Anxiety; Depression; Job satisfaction; Turnover intention; Restaurant employees; Tipped employees; Non-tipped employees